PERFORMANCE OF REGIONAL FINANCIAL INDEPENDENCE ON INCOME DISPARITY AND ECONOMIC GROWTH IN EAST JAVA PROVINCE - Muhammad Yasin; Meiril Hardi (Jurnal Ekonomi, 2022)
This good regional financial performance is due to the greater the income obtained from regional taxes, regional levies, the results of separated regional wealth management and other legitimate income and the smaller the central loan and assistance, the more independent the region. With the more independent the area, the economic growth in the area can increase. This is because the area is able to manage economically, efficiently, and effectively and the lack of policy intervention by the central government. aims: 1. To analyze descriptively the Effect of Independent Performance on Income Disparities in East Java Province. 2. Analyzing descriptively the Effect of Independence Performance on Economic Growth in East Java Province. 3. Simultaneously analyze the influence of independent performance on income disparities and economic growth in East Java Province. Analysis of the data in this study using the PLS (Partial Least Square) program version 3.0 M3 PLS (Partial Least Square) was first developed by wold as a general method for estimating the path model using latent constructs with multiple indicators. Independence Performance on Income Disparity in East Java Province is significant with t-statistic of 2,369 (> 1.96). Economic Growth on Income Disparity in East Java Province is not significant with a t-statistic of 0.062 (<1.96). Disparity of Income to Community Welfare in East Java Province is not significant with t-statistic of 0.836 (<1.96).